Environmental Stewardship and Technical Efficiency in Canadian Prairie Canola Production. (7th October 2015) - Cagdas, Ali D.; Jeffrey, Scott R.; Smith, Elwin G.; Boxall, Peter C.
Abstract : This study examines beneficial management practice (BMP) adoption and technical efficiency for canola producers in the Canadian Prairie Provinces. A Just‐Pope stochastic frontier production function is estimated using data from a survey of canola producers. Yield is modeled as a function of nutrients and precipitation. A linear inefficiency function includes farm specific variables and a set of binary variables representing BMP adoption. BMP variables for nutrient management planning and precision farming are positively related to technical efficiency while results for the other BMP indicators are mixed. Model estimates appear to be significantly influenced by moisture problems that occurred through the Prairie region during the 2011 cropping year. The study results suggest that for Western Canadian canola producers, there is potential complementarity for some BMPs in terms of improving technical efficiency while simultaneously advancing environmental stewardship.